Issues to develop tertiary education in line with regional development - Otgonkhuu, Tsedev-Ish; Altanbagana, Myagmarsuren (Proceedings of the Mongolian Academy of Sciences, 2021)
For Mongolia, which has a small population, a large territory, and abundant natural, agricultural, and mineral resources, regional development of the education sector, especially tertiary education, which is significant for population settlement, is an important issue for regional development. The purpose of this study is to optimize spatial planning of the tertiary education sector in line with regional development. This research used statistical and spatial analyzing methods to achieve the sets of research objectives. The key indicators of the tertiary education sector included a number of universities, institutes, and colleges, students, full-time teachers, new entrants, and graduates from general educational schools and the relevant datasets were collected from the National Statistical Office (NSO) and the Ministry of Education and Science (MES) covering the period from 1990 to 2019. As can be seen from research results, 92.5 per cent of tertiary educational institutions, 88.9 per cent of all employees working in the sector, 92.6 per cent of all students, and 92.2 per cent of new entrants are all located in Ulaanbaatar alone, which means that Mongolia’s tertiary education sector is overcrowded in the Capital city only. This study suggests that it is necessary to support the establishment of vocational and tertiary education institutions, research centers, institutes, and their branches outside of the capital city by first reviewing the status and functions of national and aimag-level cities, which are in line with regional and local unique and economic priorities.